2022
DOI: 10.3390/jcm11133705
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Hydrodissection with 5% Dextrose for Persistent and Recurrent Carpal Tunnel Syndrome: A Retrospective Study

Abstract: Patients with failure of primary surgery for carpal tunnel syndrome (CTS) present a frustrating clinical problem because there are no relevant treatment guidelines, and the effect of current conservative management or revision surgery is unsatisfactory. Hydrodissection with 5% dextrose is emerging as an effective treatment for primary CTS and may be an effective alternative treatment method for persistent or recurrent post-surgical CTS. We retrospectively investigated the long-term effectiveness of hydrodissec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Among the six studies of UPIT using D5W ( Table 5 ), four were double-blind RCTs [ 49 , 50 , 51 , 52 ], one investigated UPIT with D5W vs. normal saline [ 49 ], one evaluated UPIT with D5W vs. corticosteroids [ 50 ], and two compared different volumes of D5W in UPIT [ 51 , 52 ]. Of the two retrospective case series [ 73 , 74 ], one reported the long-term outcomes of UPIT with D5W [ 73 ] and another evaluated the effectiveness of UPIT with D5W in the post-surgical persistence and recurrence of CTS [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the six studies of UPIT using D5W ( Table 5 ), four were double-blind RCTs [ 49 , 50 , 51 , 52 ], one investigated UPIT with D5W vs. normal saline [ 49 ], one evaluated UPIT with D5W vs. corticosteroids [ 50 ], and two compared different volumes of D5W in UPIT [ 51 , 52 ]. Of the two retrospective case series [ 73 , 74 ], one reported the long-term outcomes of UPIT with D5W [ 73 ] and another evaluated the effectiveness of UPIT with D5W in the post-surgical persistence and recurrence of CTS [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 20th edition of Harrison’s Principles of Internal Medicine also officially lists this method as an alternative treatment for CTS [ 105 ]. Recently, a retrospective study by Chao et al [ 74 ] suggested that UPIT with D5W is clinically important with a durable effect in patients with failure of CTS surgery. They retrospectively followed 36 patients with persistent or recurrent symptoms after CTS surgery for a mean post-injection follow-up of 33 months and symptom relief of more than 50% was reported by 22 patients (61%) after a mean of 3.1 injections of UPIT with 10 mL D5W.…”
Section: Discussionmentioning
confidence: 99%
“…After removing review articles, unpublished studies, meta-analyses, case studies, practical guidelines, and books (n = 776,065), the full text of the remaining 150 articles was assessed for eligibility. Ultimately, 15 research articles were included in the review (Figure 2) [21,[34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Santoso et al administered a corticosteroid injection in one group of 15 patients and dextrose water (D5W) in another group of 15 patients, with a total of 30 patients injected [35]. D5W was also used as the principal type of injection in six studies to treat CTS [21,35,36,[40][41][42]. As previously mentioned by Santoso et al, Li et al evaluated 185 patients with CTS after D5W injection [41].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…At this point, we can only rely on a few small studies [28,29]. The largest studies so far describe the benefits of ultrasound guided injections for carpal tunnel [30][31][32]. Currently, the twentieth edition of "Harrison's Principles of Internal Medicine" textbook recommends this novel injection therapy as an alternative local treatment for carpal tunnel syndrome [33].…”
Section: Short-term and Long-term Effects Of Glucopuncturementioning
confidence: 99%